Old star clusters in the FSR catalogue - Froebrich, Dirk; Schmeja, Stefan; Samuel, D.; Lucas, Philip (Monthly notices of the Royal Astronomical Society, 2010)
We investigate the old star clusters in the sample of cluster candidates from the Froebrich, Scholz & Raftery (FSR) list. Based on photometry from the Two-Micron All-Sky Survey, we generated decontaminated colour-magnitude and colour-colour diagrams to select a sample of 269 old stellar clusters. This sample contains 63 known globular clusters, 174 known open clusters and 32 so far unclassified objects. Isochrone fitting has been used to homogeneously calculate the age, distance and reddening to all clusters. The mean age of the open clusters in our sample is 1 Gyr. The positions of these clusters in the Galactic plane show that 80 per cent of open clusters older than 1 Gyr have a Galactocentric distance of more than 7 kpc. The scaleheight for the old open clusters above the Galactic plane is 375 pc, more than three times as large as 115 pc, which we obtain for the younger open clusters in our sample. We find that the mean optical extinction towards the open clusters in the disc of the Galaxy is 0.70 mag kpc−1. The FSR sample has a strong selection bias towards objects with an apparent core radius of 30-50 arcsec and there is an unexplained paucity of old open clusters in the Galactic longitude range of 120° < l < 180°.